Calmodulin HvCaM1 Negatively Regulates Salt Tolerance via Modulation of HvHKT1s and HvCAMTA4 . Issue 4 (18th June 2020) - Shen, Qiufang; Fu, Liangbo; Su, Tingting; Ye, Lingzhen; Huang, Lu; Kuang, Liuhui; Wu, Liyuan; Wu, Dezhi; Chen, Zhong-Hua; Zhang, Guoping
Abstract : Barley calmodulin HvCaM1 regulates salt tolerance by mediating the expression of Na + transport-related HKT1 genes and the transcriptional regulation by a CaM-binding transcription activator, HvCAMTA4. Abstract: Calcium (Ca 2+ ) signaling modulates sodium (Na + ) transport in plants; however, the role of the Ca 2+ sensor calmodulin (CaM) in salt tolerance is elusive. We previously identified a salt-responsive calmodulin (HvCaM1) in a proteome study of barley ( Hordeum vulgare ) roots. Here, we employed bioinformatic, physiological, molecular, and biochemical approaches to determine the role of HvCaM1 in barley salt tolerance. CaM1s are highly conserved in green plants and probably originated from ancestors of green algae of the Chlamydomonadales order. HvCaM1 was mainly expressed in roots and was significantly up-regulated in response to long-term salt stress. Localization analyses revealed that HvCaM1 is an intracellular signaling protein that localizes to the root stele and vascular systems of barley. After treatment with 200 mm NaCl for 4 weeks, HvCaM1 knockdown (RNA interference) lines showed significantly larger biomass but lower Na + concentration, xylem Na + loading, and Na + transportation rates in shoots compared with overexpression lines and wild-type plants. Thus, we propose that HvCaM1 is involved in regulating Na + transport, probably via certain class I high-affinity potassium transporter (HvHKT1;5 and HvHKT1;1)-mediated Na + translocation in roots. Moreover, we demonstrated that HvCaM1 interacted with a CaM-binding transcription activator (HvCAMTA4), which may be a critical factor in the regulation of HKT1s in barley. We conclude that HvCaM1 negatively regulates salt tolerance, probably via interaction with HvCAMTA4 to modulate the down-regulation of HvHKT1;5 and/or the up-regulation of HvHKT1;1 to reduce shoot Na + accumulation under salt stress in barley.